Early Clinical Mapping of Submandibular Gland Fistula: A Case Report and Systematic Review - Dokania, Vivek; Ibrar, Md; Vishwakarma, Mayashankar (International Archives of Otorhinolaryngology, 2023)
Introduction Submandibular gland fistula (SGF) is a rare subset of salivary gland fistulas. It is seldom tough to diagnose them prior to surgical exploration, and it is often clinically confused with close differentials. An early diagnosis based on pertinent clinical features and focused radiological findings can be pivotal in optimal management and help prevent recurrence and avoid unnecessary investigations/interventions.Objective To review articles that discuss SGF and provide vital etiological, clinical, and imaging features of this rare entity that can aid in early clinical diagnosis.Data Synthesis An extensive review involving PubMed and Google Scholar and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards.Conclusion Submandibular gland fistula is a rare entity. It can be confused with close differentials, including branchial fistulas, if not thoroughly examined. Discharge from fistulae along with submandibular pain/tenderness and/or swelling are important diagnostic clues. A history of trauma, nodule at the site of discharge, prior submandibular disease/calculi, or discharge aggravated with food further increases a clinical suspicion. Optimal radiological investigation looking for calculi/foreign body and delineating the fistula tract is vital to affirm a diagnosis. Gland with fistula excision is a commonly advocated treatment of choice with no reports of recurrence, although conservative management and gland preserving surgery have also reported a favorable prognosis.
Keywords: salivary gland; fistula; submandibular gland